Cut-and-Transfer Technique for Ischemic Mitral Regurgitation and Severe Tethering of Mitral Leaflets - Cappabianca, Giangiuseppe; Bichi, Samuele; Patrini, Davide; Pellegrino, Pasquale; Poloni, Camillo; Perlasca, Elena; Redaelli, Marianna; Esposito, Giampiero (The Annals of thoracic surgery, 2013)
Chronic ischemic mitral regurgitation (MR) denotes abnormal function of normal leaflets resulting from left ventricular enlargement. We present the midterm results of a tailored mitral repair technique using a combination of the following subvalvular procedures: (1) detachment and reimplantation of secondary chordae on the free edge of the anterior leaflet (“cut-and-transfer” technique), (2) relocation of the posterior papillary muscle (PPM) closer to the mitral annulus, and (3) infarct plication on the lateral wall of the left ventricle. From 2008 to 2011, 49 patients with moderate to severe ischemic MR underwent coronary surgery plus mitral valve repair using the cut-and-transfer and PPM relocation techniques. All the patients received a “true-sized” semirigid complete annuloplasty ring. In 20 patients, a plication of the lateral wall of the left ventricle was performed to reduce the tethering of the mitral leaflets. The mean number of coronary grafts per patient was 3.4 ± 0.4. Hospital mortality was 2%. No patient died during 1-year follow-up and New York Heart Association (NYHA) class improved from 3.4 ± 0.5 to 1.4 ± 0.6 (p < 0.0001). The 1-year echocardiogram showed the following changes from baseline: mitral regurgitation grade (0–4) 2.9 ± 0.4 versus 0.2 ± 0.4 (p < 0.0001), left ventricular end-systolic volume index (mL/m2) 52.7 ± 13.1 versus 48.2 ± 10.1 (p = 0.07), left ventricular end-systolic index (mL/m2) 92.9 ± 16.5 versus 83.4 ± 15.9 (p <0.005), and ejection fraction (%) 37.8 ± 6.3 versus 44.2 ± 8.1 (p < 0.0001). Both clinical and echocardiographic results show that reducing the tethering of the mitral leaflets with tailored interventions on subvalvular apparatus without undersizing the mitral annulus can safely and effectively correct chronic ischemic MR.